PROFIL MISKONSEPSI SISWA KELAS XI SMK PADA MATERI GELOMBANG BUNYI BERDASARKAN HASIL THREE-TIER TEST - Elfani, Rico (2013)
The research was held in SMKN 12 Bandung with participation from 60 students as researches subject, regarding that they have been taught about sound wave by their physic's teachers. The main goal of this research is to explain profile of grade XI SMK student's misconceptions about sound wave Based on three-tier test's results. Three tier-test was employed as instrument because it can differentiate and separate the mistakes answers from students as real/genuine misconception and false misconception. Not all mistakes answers are misconceptions, they can be categorize as lack of knowledge or error that are false misconceptions. The applied researches method is cross sectional survey and data was collected by using interview and test. Some of new misconceptions about sound wave have found. After three-tier test was tested, the gained reliability value is 0.83. Based on three-tier test's results, it was founded that the largest percentage of misconception which experienced by students is about Doppler Effect. Students imagined that change of sound frequency which heard by observer is caused by his/her distance from sound's source, not because of relative motion between observer and source. Largest percentage of lack of knowledge was found on organ pipe resonance concept with percentage value 23,33 % of student. Largest percentage of error was found on diffuse reflection of sound's waves concept with percentage value 35 % of student. Keywords: three-tier test, misconception, error, lack of knowledge. Penelitian dilaksanakan di SMK Negeri 12 Bandung dengan melibatkan subjek penelitian 60 siswa kelas XI yang sudah diberikan materi pelajaran gelombang bunyi oleh guru fisika yang bersangkutan. Tujuan penelitian ini adalah untuk menjelaskan profil miskonsepsi siswa SMK kelas XI beradsarkan hasil three-tier test. Three tier test digunakan karena dapat membedakan kesalahan jawaban siswa yang merupakan miskonsepsi (mikonsepsi asli) dan memisahkannya dari kesalahan yang lain yang sering diangggap miskonsepsi (miskonsepsi palsu) yaitu lack of knowledge (kurang pengetahuan) dan error. Metode penelitian yang diterapkan adalah cross sectional survey dan pengumpulan data menggunakan teknik wawancara dan tes. Setelah three-tier test diujikan didapatkan reliabilitas sebesar 0.83. Beberapa miskonsepsi gelombang bunyi baru ditemukan dari hasil jawaban siswa pada three-tier test. Berdasarkan hasil three-tier test, ditemukan bahwa miskonsepsi terbesar yang dialami siswa adalah pada konsep efek Doppler dengan persentase 76,67%. Siswa berpikiran bahwa perubahan frekuensi bunyi yang didengar oleh pengamat disebabkan oleh jaraknya dari sumber, bukan karena gerak relatif antara pengamat dan sumber. Kurang pengetahuan terbesar dengan persentase 23,33 % pada konsep pipa organa tertutup dan terbuka dan error terbesar pada konsep pemantulan difus pada bunyi dengan persentase 35 %. Kata kunci: tes pilihan ganda tiga tingkat, misksonepsi, error , kurang pengetahuan